RAINFALL ANALYSIS USED OBSERVATION GRIDDED DATA AUTOMATIC WEATHER STATION (AWS) IN BANDUNG BASIN (Case Study Rainfall February 28th 2017 and March 9th 2017) - SARTIKA DEWI (NIM : 12813001), EUIS
The purpose of this study is to analyze a localized rain analysis using a data grid derived from AWS network data available in the Bandung Basin. The data grid is created by using ordinary kriging interpolation method. The resulting data grid has been through the verification process. Results from the grid of rain data indicate if the rain on February 28th, 2017 occurred at different times between the northern and southern part of Bandung Basin. Rain in the Bandung Basin on February 28th, 2017 is not only generated by a single convective cloud that moves, but there are three convective clouds. One convective cloud originated from the Bandung Basin itself and two convective clouds originated from areas outside the Bandung Basin. Wide rain coverage is the result of the merger of the three convective clouds. While the rain that occurred on March 9th, 2017 produced by a convective cloud that grows outside the northern part of Bandung Basin to enter the Bandung Basin.